“Managing a Department, Working with the School Dean and Staying Research Active.” - Valerie J. Watnick (Academic Chairpersons Conference Proceedings, 2016)
This session will consider and discuss the literature regarding academic chairperson/dean management styles, and best department management practices. The session will involve consideration of typical fictional scenarios potentially faced by department chairs and deans and brainstorming to flesh out management strategies that allow time for both a well-managed department and quality research by the department chairperson and other faculty. The program will involve interactive (fictional) fact-based exercises.
Keywords: Research; Leadership; Communication; Delegation; Management